The impact of acute post-extraction oroantral communications surgical treatment on patients' quality of life in early post-operative period - I. M. Got'; I. S. Sorokivskyi; Yu. O. Medvid (Zaporožskij Medicinskij Žurnal)
The research objective is to study the impact of plastic surgery different methods of acute post-extraction oroantral communications treatment on patients' quality of life in early post-operative period.